Rethinking English language teaching: didactic adaptations to incorporate ELF in the LEA-NI course at UESC - Medeiros Frossard, Elaine Cristina; Barbosa Galvão, Raquel (Árboles y Rizomas, 2025)
This paper investigates the importance of approaching English as a Lingua Franca (ELF) in the teaching of English in the Foreign Languages Applied to International Negotiations (LEA-NI) course at the Universidade Estadual de Santa Cruz (UESC), located in Ilhéus, BA, Brazil. The study aims at recognizing the relevance of teaching materials that integrate the perspective of ELF and understanding how this approach can meet the needs of the LEA-NI course. To this end, adaptations were made to activities from the New Edition Market Leader Elementary and Pre-Intermediate books with a focus on promoting linguistic and cultural diversity. The research adopts a qualitative, exploratory and bibliographical approach, based on authors such as Jenkins (2015), Seidlhofer (2011) and Siqueira (2020). The results show that introducing the ELF perspective into English teaching activities strengthens students’ autonomy, expands their intercultural competence and provides greater confidence in communication in multilingual environments, contributing to educate professionals capable of working in international negotiations. The study reinforces the relevance of a critical revision of teaching materials and the adoption of pedagogical strategies that approach the plurality of English in global contexts.
Keywords: English as a lingua franca; English language teaching; international negotiations; teaching materials